2021
DOI: 10.1111/jch.14348
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension among Mongolian adults in China: A cross‐sectional study of prevalence, awareness, treatment, control, and related factors

Abstract: The objectives of the study were to comprehend the prevalence of hypertension (HTN) and prehypertension (PHT), awareness, treatment, and control of HTN and its distribution in urban, agricultural, pastoral, and semi‐agricultural/semi‐pastoral areas, and to explore the related factors of HTN among Mongolian adults in China. From August 2018 to August 2020, a multi‐stage stratified cluster random sampling method was conducted to investigate the prevalence of HTN among Mongolian adults aged ≥18 years living in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…In these ethnic groups, the rate of Han nationality was the lowest (27.0%), while the rates of Mongolian and Tibetan were more than 30%. These results were consistent with previous studies [ 17 ]. Most of the Tibetan population in China are living in the highlands, and some publications indicated that chronic hypoxia exposure may cause a higher prevalence of hypertension [ 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…In these ethnic groups, the rate of Han nationality was the lowest (27.0%), while the rates of Mongolian and Tibetan were more than 30%. These results were consistent with previous studies [ 17 ]. Most of the Tibetan population in China are living in the highlands, and some publications indicated that chronic hypoxia exposure may cause a higher prevalence of hypertension [ 18 ].…”
Section: Discussionsupporting
confidence: 94%
“…In other words, most Mongolian families raise sheep and cattle, and their diets are primarily based on lamb, beef and dairy products (16) . Other studies have documented such eating behaviours and linked them to lack of dietary fibre intake as well as increased risks of hypertension and obesity (17,18) . Moreover, the weather and geographical characteristics of wide grasslands in West China make it not an ideal place for raising seafood, which is limited and mostly supplied from other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Each region has a unique lifestyle with specific eating habits, all of which have an impact on rates of HTN. Overlain on these variations are traditional risk factors, such as smoking, drinking and salt intake[ 33 , 34 ] plus environmental factors[ 35 , 36 ]. Results of the current study were not in accord with those of previous studies and discrepancies may be due to population and lifestyle differences.…”
Section: Discussionmentioning
confidence: 99%